Migratory movements and foraging grounds of endangered green sea turtles in South China Sea based on satellite telemetry during fishing moratorium - Yu, Dongmei; Xia, Zhongrong; Yang, Xitao; Ng, Connie Ka Yan; Yang, Kong; Wu, Zhenghao; Liu, Xiaofeng; Hu, Huijian (Frontiers in Marine Science, 2023)
The insights gained from individual tracking can improve the conservation of released young green sea turtles by providing detailed data on migration route, feeding place and habitat distribution. During the fishing moratorium from May 1 to August 16 in 2021, we used satellites to track 6 juvenile green sea turtles released from China’s Huidong Sea Turtle Nature Reserve, and located and reconstructed their migration routes and foraging sea areas. The tracking data shows that the longest tracking time is 91 days, the shortest time is 10 days, and the total tracking time is 213 days, of which three (50%) obtained tracking data for more than one month, and the total movement distances (statistics LC3-LCB) ranges from 124 to 4627 km, while the accurate movement distances (counted by dot pitch above LC0) ranged from 39.5-2331km. The average daily movement distances ranges from 3.95 to 51.4 km, and the average speed varies between 0.16 to 2.14 km/h. The green turtles released from the China Turtle Bay migrate along the northern coastline of the South China Sea or go straight to the South China Sea. After a month or so, they migrate from Huidong Turtle Bay to Hainan Lingao, Beibu Gulf and Xisha Islands. The northern coast of the South China Sea is one of the migration routes of green sea turtles. Beibu Bay, Zhanjiang Port, Daya Bay, Red Bay, Nan'ao Island, Zhelin Bay and Xisha Islands are important foraging places for green sea turtles. The protection of migration routes and important foraging grounds is one of the key measures to protect sea turtles.